MECHANISMS OF INTERACTION BETWEEN GUT MICROBIOTA AND BRAIN IN MENTAL DISORDERS - Voronina Natalya Vladimirovna (Modern American Journals, 2026)
In recent years, increasing scientific attention has been directed toward the bidirectional communication between the gastrointestinal tract and the central nervous system, known as the gut–brain axis. Emerging evidence suggests that gut microbiota play a crucial role in regulating brain development, emotional behavior, stress responses, and cognitive functions. This review explores the key mechanisms underlying microbiota–brain interactions, including neural pathways via the vagus nerve, neuroendocrine regulation through the hypothalamic–pituitary–adrenal axis, immune-mediated signaling, and microbial production of neurotransmitters and metabolites. Special emphasis is placed on the role of dysbiosis in the pathogenesis of mental disorders such as depression, anxiety, autism spectrum disorder, schizophrenia, and stress-related conditions. Additionally, the therapeutic potential of microbiome modulation through diet, probiotics, lifestyle interventions, and emerging psychobiotics is discussed. Understanding the gut–brain axis provides new opportunities for preventive and personalized approaches to mental health management.
Keywords: Gut–brain axis, gut microbiota, dysbiosis, mental disorders, depression, anxiety, psychobiotics, inflammation, neurotransmitters